ANALISIS PEMADAMAN PENERANGAN JALAN UMUM SELAMA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT DARURAT PERSPEKTIF HUKUM PELAYANAN PUBLIK: Analysis of Public Street Lighting Blackouts During the Enforcement of Restrictions on Emergency Community Activities Legal Perspective of Public Service - Ina Ismayawati; Sholikul Hadi (Constitution Journal, 2022)
The implementation of Emergency Community Activity Restrictions or Emergency PPKM is one form of policy issued by the Indonesian government during the COVID-19 pandemic. This step was taken as an effort to stop the spread of COVID-19. However, in reality, this policy reaps pros and cons in society because it is considered to have injured several aspects of public service law. The objectives to be achieved with this research are: 1) Knowing the policy of turning off Public Street Lighting (PJU) during Emergency PPKM violates the law of public service or not. 2) Knowing the application of the principles of public service in the policy of blackout of Public Street Lighting (PJU) during the PPKM Emergency. This research is a type of normative legal research. The approach used in this research consists of two kinds, namely the statutory approach and the conceptual approach. The research was conducted by identifying and reviewing selected legal issues using primary, secondary, and tertiary legal materials. After conducting an in-depth study, conclusions will be drawn in the form of legal arguments that will answer legal issues and are stated in the conclusions. This study reached the following conclusions: 1) The policy of blackout of Public Street Lighting during Emergency PPKM is still not following the ideal public service law. 2) The application of the principles of public service has not yet been fully fulfilled. maximum during the implementation of the policy. Keywords : Blackout, Public Street Lighting, Emergency PPKM, Public Service. Pemberlakuan Pembatasan Kegiatan Masyarakat Darurat atau PPKM Darurat ialah salah satu bentuk kebijakan yang dikeluarkan pemerintah Indonesia selama pandemi covid-19. Langkah ini diambil sebagai upaya untuk memutus penyebaran covid-19. Namun, realitanya kebijakan ini menuai pro dan kontra dalam masyarakat karena dianggap telah mencederai beberapa aspek dalam hukum pelayanan publik. Tujuan yang ingin dicapai dengan adanya penelitian ini ialah: 1) Mengetahui kebijakan pemadaman Penerangan Jalan Umum (PJU) selama PPKM Darurat melanggar hukum pelayanan publik atau tidak. 2) Mengetahui penerapan asas-asas pelayanan publik dalam kebijakan pemadaman Penerangan Jalan Umum (PJU) selama PPKM Darurat. Penelitian ini ialah jenis penelitian hukum normatif. Pendekatan yang digunakan dalam penelitian ini terdiri atas dua macam yaitu pendekatan perundang-undangan dan pendekatan konsep. Penelitian dilakukan dengan cara mengidentifikasi dan mengkaji isu hukum yang dipilih dengan menggunakan bahan hukum primer, sekunder, dan tersier. Setelah dilakukan pengkajian yang mendalam maka akan ditarik kesimpulan dalam bentuk argumentasi hukum yang akan menjawab isu hukum dan dituangkan dalam kesimpulan. Penelitian ini mencapai kesimpulan sebagai berikut: 1) Kebijakan pemadaman Penerangan Jalan Umum selama PPKM Darurat masih belum sesuai dengan hukum pelayanan publik yang ideal. 2) Penerapan asas-asas pelayanan publik masih belum dapat dipenuhi secara maksimal selama pelaksanaan kebijakan tersebut Kata Kunci : Pemadaman, Penerangan Jalan Umum, PPKM Darurat, Pelayanan Publik.